World Order : Reflection on the Character of Nations and the Course of History - Kissinger, Henry (GHQ, Rawaldindi Service Book Club, 2014)
Henry Kissinger offers in World Order a meditation on the roots of international harmony and global disorder. There has never been a true "world order," Kissinger observes. For most of history, civilizations defined their own concepts of order. Each considered itself the center of the world and envisioned its distinct principles as universally relevant. China conceived of a global cultural hierarchy with the Emperor at its pinnacle. In Europe, Rome imagined itself surrounded by barbarians. When Rome fragmented, European peoples refined a concept of an equilibrium of sovereign states and sought to export it across the world. Islam, in its early centuries, considered itself the world's sole legitimate political unit, destined to expand indefinitely until the world was brought into harmony by religious principles. The United States was born of a conviction about the universal applicability of democracy -- a conviction that has guided its policies ever since. Now international affairs take place on a global basis, and these historical concepts of world order are meeting. Every region participates in questions of high policy in every other, often instantaneously. Yet there is no consensus among the major actors about the rules and limits guiding this process, or its ultimate destination. The result is mounting tension. Grounded in Kissinger's study of history and his experience as National Security Advisor and Secretary of State, World Order guides readers through crucial episodes in recent world history. Kissinger offers a glimpse into the inner deliberations of the Nixon administration's negotiations with Hanoi over the end of the Vietnam War, as well as Ronald Reagan's tense debates with Soviet Premier Gorbachev in Reykjavík. He offers insights into the future of U.S.-China relations and the evolution of the European Union, and examines lessons of the conflicts in Iraq and Afghanistan. Taking readers from his analysis of nuclear negotiations with Iran through the West's response to the Arab Spring and tensions with Russia over Ukraine, World Order anchors Kissinger's historical analysis in the decisive events of our time.
Include Notes and Index
Keywords: Geopolitics -- Security, International -- World politics -- International relations